Halide anion discrimination by a tripodal hydroxylamine ligand in gas and condensed phases. Issue 36 (2nd September 2019) - Cheisson, Thibault; Jian, Jiwen; Su, Jing; Eaton, Teresa M.; Gau, Michael R.; Carroll, Patrick J.; Batista, Enrique R.; Yang, Ping; Gibson, John K.; Schelter, Eric J.
Abstract : The binding of halide anions with a tripodal hydroxylamine ligand studied in gas (mass spectrometry and DFT methods) and condensed phases revealed notable agreement. Abstract : Electrospray ionization of solutions containing a tripodal hydroxylamine ligand, H3 TriNOx ([((2- t BuNOH)C6 H4 CH2 )3 N]) denoted as L, and a hydrogen halide HX: HCl, HBr and/or HI, yielded gas-phase anion complexes [L(X)] − and [L(HX2 )] − . Collision induced dissociation (CID) of mixed-halide complexes, [L(HX a X b )] −, indicated highest affinity for I − and lowest for Cl − . Structures and energetics computed by density functional theory are in accord with the CID results, and indicate that the gas-phase binding preference is a manifestation of differing stabilities of the HX molecules. A high halide affinity of [L(H)] + in solution was also demonstrated, though with a highest preference for Cl − and lowest for I −, the opposite observation of, but not in conflict with, what is observed in gas phase. The results suggest a connection between gas- and condensed-phase chemistry and computational approaches, and shed light on the aggregation and anion recognition properties of hydroxylamine receptors.